Urban Land Grabbing: Analyzing Zones for Community Uses in Hong Kong - Mark Hansley Chua; Lawrence Wai Chung Lai (Land)
This study, as a contribution to the research on urban land grabbing (grabs) as a global phenomenon, seeks to evaluate the populist belief that developers swallow up urban land originally zoned for community purposes under Government, Institution and Community (GIC) zoning, thus depriving communities of space for their own benefit. The authors applied a systematic analysis of non-aggregate planning and development statistics to better interpret the features of the land market as regulated by zoning. Their research focuses on the salient features of redevelopment projects that enjoy successful planning applications and onsite development in GIC zones. They compared the planning and development statistics, obtained from the Planning Department’s website, of 425 approved GIC projects with those of the 261 Comprehensive Development Area (CDA) zone projects. Subject to the limitations of the data collected, the results qualify a negative view of land oligarchs (powerful land developers) who sought land under unitary ownership obtained in the past at nominal land premiums for quick windfalls. Particularly, GIC redevelopments were found to have proceeded much faster than CDA developments and, hence, were a natural attraction to developers, which were diverse, not exclusively private, and produced a few urban innovations during the redevelopment process.